Disorientasi Seksual Sebagai Alasan Fasakh Perkawinan (Analisis Putusan No.300/Pdt.G/Pa.Pyb) - Betawi, Usman (-, 2024)
Abstract: The research analyzes a court decision regarding the annulment of a marriage filed by a wife due to her husband, who is a homosexual, concealing his sexual orientation before marriage. The study delves into legal perspectives and Islamic Family Law (KHI) regarding marriage annulment due to sexual disorientation, judicial considerations in the decision, and the validity analysis of sexual disorientation as a ground for marriage annulment (fasakh). This research employs a juridical-normative approach with a qualitative method. The study reveals that Indonesia lacks a specific law governing the annulment of marriage due to sexual disorientation. However, drawing upon Article 72 (2) of the Compilation of Islamic Law (Kompilasi Hukum Islam) and the principle of "dar'ul mafasid muqoddam ala jaib al-masalih" (prioritizing the avoidance of harm over the pursuit of benefit), the judge ruled to annul the marriage due to indications of fraud. The annulment was deemed appropriate as continuing a marriage with someone experiencing sexual disorientation could potentially harm one of the parties and hinder the attainment of the marriage's objectives of tranquility, love, and compassion (sakinah, mawaddah, warahmah). The study recommends the revision or addition of more specific regulations to provide legal certainty and protection for those harmed in a marriage due to sexual disorientation. Abstrak: Penelitian ini menganalisis Putusan No. 300/Pdt.G/2022/PA.Pyb mengenai gugatan pembatalan perkawinan yang diajukan seorang istri karena suaminya, seorang homoseksual, menyembunyikan disorientasi seksualnya sebelum pernikahan. Masalah penelitian meliputi pandangan Undang-undang dan KHI tentang pembatalan nikah karena disorientasi seksual, pertimbangan hukum hakim dalam putusan tersebut, serta analisis validitas disorientasi seksual sebagai alasan pembatalan nikah (fasakh). Metodologi yang digunakan adalah yuridis normatif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa di Indonesia belum ada UU yang mengatur secara khusus pembatalan nikah karena disorientasi seksual. Namun, berdasarkan Pasal 72 ayat (2) Kompilasi Hukum Islam dan asas dar mafasid muqoddam ala jaib al-masalih, hakim memutuskan pembatalan pernikahan karena indikasi penipuan. Pembatalan nikah dianggap tepat karena meneruskan pernikahan dengan seseorang yang mengalami disorientasi seksual dapat merugikan salah satu pihak dan menghambat tercapainya tujuan pernikahan yaitu sakinah, mawaddah, warahmah. Penelitian ini merekomendasikan perlunya revisi atau penambahan peraturan perundang-undangan yang lebih spesifik untuk memberikan kepastian hukum dan perlindungan bagi pihak yang dirugikan dalam pernikahan akibat disorientasi seksual.